Synthesis of New Pyrimidine Derivatives From 3-Acetylcoumarin–Chalcone Hybrid and Evaluation Their Antimicrobial Activitغe their antimicrobial activity y - Hassan, Tuka; Muthanna Saadi Farhan (Iraqi Journal of Pharmaceutical Sciences, 2024)
3-coumarin/chalcone B1/B2/B3 hybrids served as malleable antecedents for the development of novel bioactive pharmacophores. In this study, the matching coumarin-chalcones hybrid was obtained from 3-acetylcoumarin (comp A) via condensation with several aromatic aldehydes in ethanolic piperidine solution. To further modify these hybrids, we reacted them with thiourea in the presence of base in ethanol, yielding pyrimidine derivatives C1, C2, and C3. Their chemical characteristics and spectroscopic data were used to characterize the newly synthesized heterocyles. The antibacterial efficacy of all freshly produced compounds was tested. Compound (C3) was shown to have the highest antibacterial activity against both gram positive and gram negative bacteria, whereas compound (C2) displayed a moderate antibacterial activity and compound C1 had low activity. C1,C2,C3 were shown antifungal activity as compared to fluconazole that showed antifungal efficacy against C. ablicans.